School Adjustment Problems of Fifth Graders As a Risk Factor in Learning Difficulties - Permiakova, M (KnE Life Sciences, 2018)
In recent years, there has been a tendency in Russia to separate primary school from secondary one; gymnasiums and lyceums where children are recruited in the fifth grade through a competitive examination start operating. Despite the fact that such schools enroll children from prosperous families who perform well at school, some of them start experiencing learning difficulties resulting in dramatic decrease in academic performance, behavioral problems, and health deterioration. One of the risk factors for these problems is the difficulties of adjusting to a new school, conditioned by agespecific psychological and physiological conditions of fifth graders and pedagogical factors. The purpose of this study is to increase awareness of fifth graders school adaptation, collect empirical data, by examining the relationship between its various components, as well as self-esteem. The present study explored 144 fifth graders aged 10-11 (74 boys and 70 girls) and their 6 class tutors (homeroom teachers). Measures: School Anxiety Questionnaire (B.N. Phillips), expert evaluation, «Sociometry» ( J.L. Moreno), self-esteem methodology called «Ladders». The results of the study into academic, social and psychological aspects of fifth graders School adjustment showed that the period of adaptation is characterized by decreased academic performance compared to the fourth grade while a third of the subjects lacked interest in studying. 39 % of fifth graders showed a low sociometric status. More than half of the students (55 %) are dissatisfied with their relationships with their classmates. An increased level of school anxiety is typical for 25% of fifth-graders. The main causes of school anxiety are fear of self-expression, problems with the teacher, fear of not meeting the expectations of others. Factor analysis proved a three-fold structure of school adaptation. The correlation analysis showed that academic adaptation is related to all components of school adaptation, whereas social and psychological components are not linked. 55 % of fifth-graders have low or poor self-esteem. They are most dissatisfied with their lack of authority among their classmates and their appearance. Factor analysis demonstrated that the self-esteem of fifth graders in the period of adaptation to secondary school is more connected to the indicators of the social component of adaptation. Teachers adequately evaluate only student performance and behavior, but not their sociometric status, school anxiety, and interest in learning. This complicates the identification of the problem and timely assistance to the fifth graders with difficulties in social and psychological adaptation. Keywords: school adaptation, learning difficulty, fifth-graders, self-esteem, school anxiety, sociometry